"Classroom Techniques To Develop Students' EnglishReading Skills: A Naturalistic Study At Smp Muhammadiyah 1 Surakarta" - Andina, Ayu, Prof. Dr. Endang Fauziati, M. Hum (2016)
AYU ANDINA.A320120117. CLASSROOM TECHNIQUE TO DEVELOP STUDENTS' ENGLISH READING SKILLS: A NATURALISTIC STUDY AT SMP MUHAMMADIYAH 1 SURAKARTA. Research Paper. School of Teaching Training and English and Education Muhammdiyah University of Surakarta 2016. This study is aimed at describing (1) classroom technique used by the teacher to develop students' English reading skill (2) the purpose of each classroom technique (3) the teacher's role (4) the student's role. This type of the research is descriptive qualitative research, especially naturalistic study. The technique of collecting data are observation and interview. The result of this study shows that there are some classroom techniques used by the teacher to develop students' English reading skill, especially reading skill such as: reading aloud, recognizing word meanings, translation, answering questions, repetition, recognizing sentence structure, and silent reading. The teacher has roles as controller, as organizer, as prompter, as resource, as tutor, as observer, and as model. The students has roles as planner, as group, as tutor, as monitor and evaluator. The conclusion of this study is that the English teacher at SMP Muhammadiyah 1 Surakarta used various classroom techniques in the teaching-learning process. It can develope the students' English skill, especially in reading skill. By using various classroom techniques can make students interested and enjoy learning English language. Students become more active and creative in teaching reading skill. Based on the result, classroom technique used by the teacher is very important to make the students interested and enjoy with the teaching-learning process of English reading skill. Key words: Classroom techniques, teacher's role, student's role.